2015
DOI: 10.1007/s10853-015-9435-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of manganese and cobalt ions on flame retardancy and thermal degradation of bio-based alginate films

Abstract: Bio-based cobalt alginate and manganese alginate films were prepared by a facile ionic exchange and casting approach. Their flame retardancy, thermal degradation, and pyrolysis properties were investigated by vertical burning (UL-94), limiting oxygen index (LOI), thermogravimetric analysis, microscale combustion calorimetry (MCC), thermogravimetric analyzer coupled with Fourier transform infrared analysis (TG-FTIR), and pyrolysis-gas chromatography-mass spectrometry (Py-GC-MS). It showed that cobalt alginate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…It has been known that alginate fibers and films have flame retardant properties without any addition of other flame ratardants [14][15][16][17][18][19][20] . Xia et al [15,16] and zhu et al [17][18][19][20][21] have investigated the effects of divalent and trivalent metal cations on the flame retardant properties, thermal degradation properties and pyrolysis properties of alginate fibers and films. The results indicated that divalent and trivalent metal ions improved the flame retardancy of alginate fibers and films, and that the addition of divalent metal ions and aluminum ions reduced the type of pyrolysis products of alginates.…”
Section: Introductionmentioning
confidence: 99%
“…It has been known that alginate fibers and films have flame retardant properties without any addition of other flame ratardants [14][15][16][17][18][19][20] . Xia et al [15,16] and zhu et al [17][18][19][20][21] have investigated the effects of divalent and trivalent metal cations on the flame retardant properties, thermal degradation properties and pyrolysis properties of alginate fibers and films. The results indicated that divalent and trivalent metal ions improved the flame retardancy of alginate fibers and films, and that the addition of divalent metal ions and aluminum ions reduced the type of pyrolysis products of alginates.…”
Section: Introductionmentioning
confidence: 99%
“…1 and Table 1, the addition of alginate fiber reduced T initial and T max of cotton/alginate fabric to 240 and 348°C, respectively. This result indicated that the addition of alginate fiber decreased the thermal stability properties of cotton fabric, and the reason for this phenomenon was that the thermal stability properties of alginate fiber were worse than those of cotton fiber [26][27][28][29][30]. Or calcium ion, which was from alginate fiber, might result in this phenomenon.…”
Section: Resultsmentioning
confidence: 95%
“…This phenomenon might be attributed to the addition of alginate fiber. According to the previous papers [26][27][28][29][30], T max s of alginate fibers and films were lower than 300°C, and the addition of metal ions further decreased T max of alginate. What is more, the addition of metal ions might catalyze some chemical reactions in the thermal degradation process of alginate and cotton.…”
Section: Flammability Versus Cone Testmentioning
confidence: 81%
See 2 more Smart Citations